Optimum insulation design for buried utilities subject to frost action in cold regions using the Nelder-Mead algorithm - Liu, Hongwei; Maghoul, Pooneh; Shalaby, Ahmed (International journal of heat and mass transfer, 2019)
•Neglecting the phase change effects leads to an erroneous design of the insulation.•Mass transfer is negligible for predicting the temperature and water content.•Using granular soil (sand) as backfill is more critical than clay.•The Nelder-Mead algorithm is effective to determine the optimum design. Frost action in soils can cause detrimental damage to buried utilities, such as water and gas pipes. One of the promising approaches to protect buried utilities against frost damage and reduce the excavation cost is to install thermal insulation over and around the pipe. This paper considers two different conductive heat transfer models, with and without the effect of soil pore-water phase change, as well as a heat and mass transfer model for freezing soils to investigate the effectiveness of insulation systems for frost protection of buried pipes. It was found that the latent heat released during the phase change significantly affects the heat transfer process and that the impact of phase change on insulation design should not be overlooked. Furthermore, by comparing numerical results to field measurement data, it is found that the mass transfer has an insignificant effect on the temperature and unfrozen water content distribution in the frost-susceptible foundation soil. A parametric study was carried out to assess the effects of different factors such as the backfill materials, geometry, total length, thickness of insulation, distance between pipe and insulation as well as the burial depth of pipe on the thermal performance of insulation. Finally, the Nelder-Mead algorithm was implemented to determine the optimum insulation design so that the overall cost is minimized while the pipe is protected from freezing.